A robot motion planner for 6-DOF industrial robots based on the cell decomposition of the workspace - Ramer, Christina; Reitelshöfer, Sebastian; Franke, Jörg (IEEE ISR 2013, 2013)
This paper describes an autonomous robot motion planner for 6-DOF industrial robots based on the approximate cell decomposition of the workspace. Known obstacles lead to a hierarchical decomposition up to a predefined degree of the start cell which contains the whole robot workspace. A connectivity tree is searched for the shortest path from the start to the goal position for the Tool Center Point (TCP) of the robot. Center points and points between adjacent cells are used as interpolation points for the robot's path. All possible configurations are calculated for these points and checked for absence of collisions and compliance with kinematic constraints. Subsequently paths between possible configurations of interpolation points are checked for feasibility. If points cannot be reached artificial obstacles are constructed and the work space model is updated.
Keywords: cellular manufacturing; collision avoidance; industrial robots; interpolation; mobile robots; robot kinematics; trees (mathematics); 6-DOF industrial robots; TCP; adjacent cells; autonomous collision free path planning; autonomous robot motion planner; connectivity tree; interpolation points; kinematic constraints; path planning problem; tool center point; work space model; workspace cell decomposition; Automation; EMTP; Gold; Mars; Planning; Service robots; 6-DOF industrial robot; cell decomposition method; operational space planner; robot motion planner